Resilience on the Run: an evaluation of a well‐being programme for medical interns. Issue 1 (14th January 2020) - Forbes, Malcolm; Byrom, Lisa; van der Steenstraten, Ira; Markwell, Alex; Bretherton, Holly; Kay, Margaret
Abstract: Background: Junior doctors experience high rates of psychological distress and burnout. System‐level interventions are one strategy to reduce psychological distress in junior doctors. Unfortunately, few of these interventions have been evaluated. Aim: To evaluate the acceptability and effectiveness of a resilience and well‐being programme designed for junior doctors. Methods: A prospective cohort study of 24 medical interns at a teaching hospital in regional Queensland with a control group of 29 medical interns at a second teaching hospital in regional Queensland. Survey instruments to assess psychological distress, the ProQOL and K10, were completed at baseline, at the completion of the well‐being programme, and 3 months after the completion of the well‐being programme at both sites. Results: The intervention site had an older cohort and fewer participants had a regular general practitioner compared to the control site. Both groups had moderate levels of psychological distress. Insufficient numbers of participants completing the instruments at the two sites meant that it was not possible to demonstrate differences between the groups; however, the trends were promising. Qualitative evaluation data supported these trends, indicating that the Resilience on the Run programme was positively received and provided useful skills to junior doctors. Conclusion: Well‐being programmes benefit medical interns; introducing new knowledge and skills for effectively identifying and managing personal and workplace stressors that can contribute to psychological distress.